Economic growth, increasing productivity of SMEs, and open innovation - Batara Surya; Firman Menne; Hernita Sabhan; Seri Suriani; Herminawaty Abubakar; Muhammad Idris (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The empowerment of small and medium economic enterprises will drive economic growth. The purpose of this study is to analyze (1) how economic growth works as a determinant of increasing the productivity of small and medium enterprises; (2) the influence of government policies, business capital support, and the strengthening of human resource capacity on the development of small and medium enterprises (SMEs); and (3) strategies to increase business productivity and the sustainability of SMEs. We used a sequential explanatory design, which is a combination of quantitative and qualitative research, and data were obtained through observation, in-depth interviews, surveys, and documentation. The results of the study indicate that economic growth coupled with technological innovation will boost the productivity of economic enterprises and increase people's welfare. Government policies, business capital support, and human resource capacity strengthening simultaneously have a positive effect on the development of SMEs, with a determination coefficient of 97.6%. Based on the results of this study, an economic growth strategy based on technological innovation is recommended for government decision making as an effort to increase the productivity of community economic enterprises in Makassar City, Indonesia.
Keywords: 650; business productivity; economic business sustainability; economic growth; public welfare